Modification Of Polymer Based Dentures On Biological Properties: Current Update, Status, And Findings - Durratul Aqwa Mohd Farid; Nur A’fifah Husna Zahari; Zulfahmi Said; Mohd Ifwat Mohd Ghazali; Lee Hao-Ern; Syazwani Mohamad Zol; Sami Aldhuwayhi; Muhammad Syafiq Alauddin (MDPI, 2024)
Indexed by WOS/Scopus/ERA